PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH TERHADAP MINAT BACA PADA MATA PELAJARAN SKI KELAS XI AGAMA DI MAN 2 BANYUWANGI - Astuti, Fahmi Yuli; Faishol, Riza; Trianingsih, Rima (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2020)
The study was backed by a low interest in the students' reading of SKI subjects. The use of this library is a new strategy in learning as an effort to improve the quality of learning by synergize between learning activities and libraries as a media source and learning media. The study aims to determine whether or not the influence of the school library is influenced by the reading interest in the class XI religious SKI subjects in MAN 2 Banyuwangi. The type of research used is a correlational descriptive method of using a quantitative approach. To collect research data, authors use observation methods, interviews, polls and documentation. The subject of this study amounted to 41 respondents taken through probability sampling data retrieval techniques and cluster sampling instruments. The data analysis techniques used are validity tests and reliability tests.